Training Simulator Batch Polystyrene Reactor - Shahidan, Mohd Syakir (Universiti Sains Malaysia, 2022)
This study is aimed to produce some sets of coding that shown same results as other researchers via different coding language. Thus, a case study on polystyrene reaction in a batch reactor was conducted by applying Ordinary Differential Equation (ODE) into a software named Python Programming Language. To ensure the success of the case study, the review on the development of virtual laboratories and simulations through literatures were a must. A lot of literatures were explaining about their initiatives towards digitalization era by constructing and applying virtual-laboratory-and-simulation-based for their studies. The efforts were supported by realizing the benefit of digitalization, which can save a lot of money, time and energy for the efficient way. ODE function was fully explored about its correct way of coding, technique and correct annotation of Python that make it differ from other languages. Case study of polystyrene reaction in the batch reactor was conducted by referring to other literatures with same-alike case study. The reaction use 2, 2’ azobisisobutyronitrile catalyst (AIBN) catalyst as an initiator. The monomer conversion, initiator conversion and initiator concentration were the most important criteria that were being studied.